The shadow economy and shadow labor force: a survey of recent developments - Schneider, Friedrich (Bonn, 2014)
"This survey presents the various methods to estimate the size of the shadow economy, their strengths and weaknesses and the estimation results. The purpose of the survey is threefold. Firstly, it demonstrates that no ideal method to estimate the size and development of the shadow economy exists. Because of its flexibility, the MIMIC method used to get macro-estimates of the size of the shadow economy is discussed in greater detail. Secondly, the paper focuses on the definition and causal factors of the shadow economy as well as on a comparison of the size of the shadow economy using different estimation methods. Thirdly, estimations of the size of the shadow economy and shadow labor force are presented and discussed."